Economic optimization from fleets of aero-derivative gas turbines utilising flared associated gas - Obhuo, M.; Aziaka, Duabari S.; Osigwe, Emmanuel O.; Emmanuel, O. A.; Pilidis, Pericles (Elsevier, 2020)
Associated gas is been wasted to flaring in some parts of the world. The use of these flared gases for both industrial and economic purposes would be very beneficial. This paper presents the development of a model for optimizing the economic return of fleets of gas turbines utilizing flared associated gas. The paper further analyzed the impact of gas turbine degradation on the optimized divestment times of the redundant engines and the economic use of associated gas. Hypothetical but realistic gas turbines were modeled using the Cranfield University performance simulation tool, TURBOMATCH. In furtherance with the investigation, the Techno-Economic and Environmental Risk Assessment (TERA) framework has been adopted for a broad and multi-dimensional optimization of the economic return from the fleets. The results were employed in three degradation scenarios (optimistic, medium, and pessimistic) within the TERA framework to generate economic models. Genetic Algorithm (GA) in MATLAB was used in carrying out optimization to maximize the economic benefit. The result showed that an increase of 1.0% and 1.6% in the energy and net present value (NPV) respectively of the optimized clean fleet as against the baseline were achieved. The economic performance of the fleets shows the optimized fleet (clean) having the highest NPV of $2.84b and the pessimistic degraded fleet having the least NPV of $2.39b. More results revealed that degradation reduced the NPV of the project by 4.0%, 9.1%, and 15.8% for the three different degradation scenarios. This paper has proposed a model that can be used for the profitable economic utilization of associated gas which would be useful to gas turbine operators and investors
Keywords: net present value; fleet composition; degradation